Experimental and computational analysis of initiation and propagation of shear bands in bulk metallic glasses. (10th April 2019) - Abeygunawardana-Arachchige, G; Nekouie, Vahid; Bell, Andy
Abstract: Shear bands (SBs) play a key role in the mechanical deformation of Bulk Metallic Glasses (BMGs). The key to obtaining an insight into the shear band mechanism is to understand the root cause of shear band initiation and propagation. SB initiation is a difficult event to capture, considering the negligible macroscopic ductility of BMGs. It is the premature shear localisation in the nano scale which is responsible for the noticeable brittle nature in the macro-scale. Plastic deformation of BMGs occurs due to the formation of highly localised SBs of approximately10–20 nm in thickness. These then propagate at a velocity of around 100 ms −1 and results in catastrophic failure in both tension and compression due to the micro-cracks formed through the coalescence of the nano voids. This study develops a technique to capture the early initiation of SBs through a wedge indentation test. The work found that incremental loading (a definite load applying incrementally by 1 kN in stages) did not affect the overall mechanical response of the BMG material, indicating that SB evolution can be examined with an incremental indentation test. A predictive numerical model for SB initiation and propagation in BMGs is presented using two approaches: a strain gradient model and an integral-type non-local approach employing the Vermeer–Brinkgreve modelling strategy(Strömberg, Ristinmaa 1996). Comparisons are made between the outcomes of physical tests and numerical modelling to obtain an insight into the relative merits.